Factors Associated with the Success Rate of Endoscopic Retrograde Cholangiopancreatography with Standard Technique followed by Laparoscopic Cholecystectomy in the Management of Choledocholithiasis: A Single-Center Experience - Konsue, Chayanon; Eurboonyanun, Chalerm; Ruangwannasak, Somchai; Eurboonyanun, Kulyada; Srisuk, Tharatip; Satitkarnmanee, Egapong; Aphinives, Potchavit; Sripanuskul, Anan (Journal of Digestive Endoscopy, 2020)
Background Choledocholithiasis is the most common benign biliary disease. Endoscopic retrograde cholangiopancreatography (ERCP) followed by laparoscopic cholecystectomy (LC) has been the first-line therapy in recent years, although laparoscopic common bile duct exploration has promising results. This retrospective study aimed to define the factors associated with biliary clearance by standard ERCP technique and conversion rate of LC.Materials and Methods We retrospectively evaluated the records of 217 choledocholithiasis patients who had undergone ERCP with stone removal by the standard technique from 2010 to 2018. A failed ERCP was defined when the first ERCP session could not remove the stones . The number of patients who later underwent open cholecystectomy or LC was also recorded. Conversion was defined when LC had to be converted OC.Statistical Analysis Student’s t-test was used for the comparison of continuous variables. Nominal variables were analyzed using Pearson’s chi-square test or Fisher’s exact test. Binary logistic regression was performed for multivariate analysis.Results The rate of successful biliary clearance was 81.1%. Of the patients, 109 (50.2%) had difficult stones. Increasing age (p = 0.004), increasing number (p = 0.001), and increasing size of stone (p < 0.001) were the three significant factors that were associated with the failure of biliary clearance. The difficult stone group had a higher failure rate of ERCP and a higher conversion rate of LC compared with the easy stone group (p = 0.001 and p = 0.027, respectively).Conclusions ERCP with the standard technique is a highly effective and safe management option for patients with common bile duct (CBD) stones. The difficult stone group was found to be an independent risk factor that affected the success rate of both ERCP and the following LC. Difficult stone criteria should be assessed to identify a patient who might benefit from laparoscopic CBD exploration.
Keywords: CBD stones; ERCP; choledocholithiasis; standard technique; difficult stones; endoscopic retrograde cholangiopancreatography; laparoscopic cholecystectomy; conversion